2016
DOI: 10.3988/jcn.2016.12.4.452
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric and Upper Body Parkinsonism in Patients with Idiopathic Normal-Pressure Hydrocephalus

Abstract: Background and PurposeOur aims were to analyze the characteristics of parkinsonian features and to characterize changes in parkinsonian motor symptoms before and after the cerebrospinal fluid tap test (CSFTT) in idiopathic normal-pressure hydrocephalus (INPH) patients.MethodsINPH subjects were selected in consecutive order from a prospectively enrolled INPH registry. Fifty-five INPH patients (37 males) having a positive response to the CSFTT constituted the final sample for analysis. The mean age was 73.7±4.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…The incidence of the classical triad is unknown; however, the presence of three concomitant symptoms has been reported in approximately 60% of cases 3 , although the triad is not required for a diagnosis of INPH 3 . Ishii et al 22 and Kang et al 23 reported that the presence of parkinsonism characteristics was frequent in patients with INPN. However, consistent with findings from another Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of the classical triad is unknown; however, the presence of three concomitant symptoms has been reported in approximately 60% of cases 3 , although the triad is not required for a diagnosis of INPH 3 . Ishii et al 22 and Kang et al 23 reported that the presence of parkinsonism characteristics was frequent in patients with INPN. However, consistent with findings from another Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Tsakanikas D et al reported that these upper extremity motor tests may be useful as sensitive markers of change after shunt placement in iNPH patients (e.g., line tracing tasks) [22]. Kang et al reported the upper limb motor function was improved after CSF TT and shunting and correlated with the gait parameters [7]. Liouta E et al also found that nger tapping improvements after CSF TT were useful for the differential diagnosis and prediction of shunt treatment outcomes [35].…”
Section: Discussionmentioning
confidence: 99%
“…Normal pressure hydrocephalus (NPH) patients present disturbances in gait and balance, cognition and/or control of urination with neuroimaging characterized by enlargement of the cerebral ventricles [1][2][3]. Typically, gait disturbance in NPH patients is the initial and most prominent symptom [4,5], but motor impairments can also extend to include upper extremity dysfunction [6][7][8][9]. Cognitive impairment in NPH patients is generally characterized by frontal system de cits that may include slowing of information processing, task shifting, reduced learning and executive abilities [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al 1 have illustrated asymmetric and upper-body parkinsonism signs in detail via follow-up clinical assessments [before and after cerebrospinal fluid-tap test (CSFTT)] in a large number of patients with idiopathic normal-pressure hydrocephalus (INPH). I would like to make some comments in order to add new perspectives to aid the understanding of that report.…”
mentioning
confidence: 99%
“…As also emphasized in the report, a probable explanation for the motor function recovery in INPH could be the reversible suppression of frontal periventricular corticobasal ganglia-thalamo-cortical circuits. 1 It has also been suggested that postsynaptic D2 receptors in the putamen can be damaged by hydrocephalus, and that a pressure load on the midbrain and the floor of the third ventricle may result in parkinsonian symptoms in patients with severe NPH. 7 However, conflicting with this hypothesis, the patients in Kang et al 1 did not have severe NPH-their score on the INPH grading scale was 5.7±1.9 (mean±SD).…”
mentioning
confidence: 99%